Pengembangan Media Pembelajaran Poster Menggunakan Smartphone Untuk Meningkatkan Pemahaman Sejarah Siswa Pada Pembelajaran Sejarah Kelas X IPS 5 SMA Negeri 15 Batam - Elisa Elisa; Bedriati Ibrahim; Suroyo Suroyo (CHRONOLOGIA, 2023)
This research produces a learning tool or media which is to improve students' understanding of history in learning history with indicators that students are capable of interpreting, exemplifying, classifying, summarizing, concluding, differentiating, and explaining. This development research uses the ADDIE model with the stages of Analysis, Design, Development, Implementation, Evaluation. The validation results of material experts with an average score of 4.53, question experts with an average score of 4.6, media experts with an average score of 4.83 in the ''Very Eligible'' category, while for the assessment of class X IPS 5 students of SMA Negeri 15 Batam as a user obtained a value with an average score of 4.65 ''Very Eligible'' used in the learning process. The results of the tests carried out by students at the pretest with a value of 57.8 and continued with the posttest with a result of 85.7. That way it shows students can recall the material that has been studied and answer correctly the questions given by the teacher. The Normalized Gain value was 68.9 in the "Effective Enough" category. From this information, it shows that the use of posters to increase students' understanding of history is ''Quite Effective'' used in history learning.